Asian eclipise : - Backman, Michael (J. Wiley & Sons (Asia), 1999)
Asian Eclipse Exposing the Dark Side of Business in Asia Asia was a shining star in the world economy for most of the 1980s and 1990s. The secrets of its success were often a subject of intense debate. Plaudits cited Japanese economic power, Confucian work ethics, the freeing of China's markets, Eastern ingenuity and the powerful overseas Chinese guanxi networks. Critics were dismissed as ignorant of Asian values. But behind the facade lay a darker, more sinister truth. In this remarkable account, leading analyst Michael Backman tears away the myths of Asian business and reveals the dark side of the Asian success story. From endemic corruption to rampant cronyism, Asian Eclipse is a tale of capitalism gone sour, it names the perpetrators and offers timely advice on what is really needed for Asia to clean up its act. It will remain an indispensable guide to the complexities of corporate Asia for years to come. Highlights include: